PREDIKSI EROSI PADA LAHAN PERTANIAN DI SUB DAS KRUENG SIMPO PROVINSI ACEH - Fitri, Rini (Universitas Jambi, 2011)
ABSTRACTErosion on agricultural land decreased production of agriculture, and it will decline the incomes of farmers. The aims of the research is to predict erosion and Etol at each units of land at Krueng Simpo Sub watershed that is used as agricultural land. The method use in the research is survey method that consist three fase namely, preparation and ground check the map units of land to determine the units of observation, and predict erosion using USLE model. The result shows that use of cultural land at Krueng Simpo Sub watershed causes erosion on monoculture of agricultural land (90,92 tone/ha/year) has exceeded Etol (31,80 tone/ha/year). Therefore, improvement, changes in cropping patterns, and application of alternative agrotechnology to minimize predictive value erosion that will accur, and enhance the agricultural corservation.